Peran Badan Usaha Milik Desa (BUMDes) dalam Pengembangan Desa Wisata di Desa Ponggok Kecamatan Polanharjo Kabupaten Klaten - Dwi Hastutik; Dwiningtyas Padmaningrum; Agung Wibowo (Universitas Sebelas Maret, 2021)
Village-Owned Enterprise (BUMDes) is pillars of village economic activities that function is as social institutions and commercial institutions. An understanding of the role of BUMDes is useful for analyzing the role of BUMDes in the development of tourist villages. The role studied is in the form, the role of awareness (conscientization), the role of community organizing, and the role of delivery of human resources (resource delivery). The objective of the study is to analyze: (1) the process of forming a tourism village (2) the role of the BUMDes in the development of a tourism village. The basic method of research is descriptive qualitative. The research location was determined intentionally, Ponggok Village, Polanharjo District, Klaten Regency. Data analysis used data reduction, data display (data display), and drawing conclusions or verification. Data validity was done by source triangulation and technique triangulation. The results of the study showed that: (1) the process of the formation of the Ponggok Tourism Village began with a pennant in Ponggok Village which was previously only used for daily needs. Over time the village government of Ponggok was aware of the tourism potential in the area. To support the development of a tourism village, the Ponggok Village government collaborated with the academy, SAR (search and rescue) team, and diving team to explore tourism potential. (2) the role of BUMDes in the development of Tourism Village seen by three things, they were the conscientization role, which was carried out with socialization activities and proof of work, the role of community organizing, channeling aspirations and the division of labor into business units, and the role of delivery of human resources (resource delivery), which was training activities carried out together with other parties such as banking and other academics.